The Geographical Factors of Physical Tourism in the Hail Governorate - Alshammari, Basheer Obaid (Journal of Humanities & Social Sciences, 2022)
This study aims to recognize the geographic factors of natural tourism in Hail governorate, northern Saudi Arabia, and bringing up these major attractions which are considered main natural tourism destinations for Hail residents and neighboring regions such as Al-Qassim, Al-Madinah Al-Munawara, Al-Jawf, and Tabuk. These factors include mountains, valleys, plains, lava fields, sands, and wild parks. The study follows an analytical descriptive survey method, which helps identify natural tourism's most critical components and potentials in the study area. As a result of the study, there are several eco-geographical components that can play a vital role in the development of ecotourism in the Hail region, such as the mountains, with its agricultural villages and valleys descending from these mountains and soft sands that tourists visit to spend their free time during their weekends and seasonal.
Keywords: Hail; Natural attractions; Ecotourism; Mountains; valleys